Adherence Measured Using Electronic Dose Monitoring is Associated with Emergent Antiretroviral Resistance and Poor Outcomes in People with Human Immunodeficiency Virus/AIDS and Multidrug-Resistant Tuberculosis . (30th March 2022) - Bateman, Mark; Wolf, Allison; Chimukangara, Benjamin; Brust, James C M; Lessells, Richard; Amico, Rivet; Boodhram, Resha; Singh, Nalini; Orrell, Catherine; Friedland, Gerald; Naidoo, Kogieleum; Padayatchi, Nesri; et al.
Abstract: Background: Medication adherence is known to challenge treatment of human immunodeficiency virus (HIV)/AIDS and multidrug-resistant tuberculosis (MDR-TB). We hypothesized that adherence using electronic dose monitoring (EDM) would identify an antiretroviral therapy (ART) adherence threshold for emergent ART resistance and predict treatment outcomes in patients with MDR-TB and HIV on ART and bedaquiline-containing TB regimens. Methods: A prospective cohort of adults with MDR-TB and HIV on ART and initiating MDR-TB treatment with bedaquiline were enrolled at a public hospital in KwaZulu-Natal, South Africa (PRAXIS Study). Participants received separate EDM devices that measure adherence to bedaquiline and ART (nevirapine or lopinavir/ritonavir). Adherence was calculated cumulatively over 6 months. Participants were followed through completion of MDR-TB treatment. HIV genome sequencing was performed at baseline and 2 and 6 months on samples with HIV RNA ≥1000 copies/mL. Results: From November 2016 through February 2018, 198 persons with MDR-TB and HIV were enrolled and followed (median, 17.2 months; interquartile range, 12.2–19.6). Eleven percent had baseline ART resistance mutations, and 7.5% developed emergent ART resistance at 6 months. ART adherence was independently associated with ART resistance and mortality. Modeling identified a significant ( P < .001), linear association between ART adherence and emergent resistance, suggesting a strong association without a specific threshold. Conclusions: Our findings highlight the need for ART resistance testing, especially in patients with MDR-TB and HIV, which is currently not the standard of care in resource-limited settings. Despite short follow-up duration, reduced ART adherence was significantly associated with emergent resistance and increased mortality. Clinical Trials Registration: NCT03162107. Abstract : In this prospective study, reduced adherence to antiretroviral therapy was associated with emergent drug resistance and increased mortality in patients with human immunodeficiency virus and multidrug-resistant tuberculosis. Targeted interventions are needed to improve adherence and reduce resistance emergence and mortality.